Chronic psychosocial stress and experimental pubertal delay affect socioemotional behavior and amygdala functional connectivity in adolescent female rhesus macaques. (May 2021) - Pincus, Melanie; Godfrey, Jodi R.; Feczko, Eric; Earl, Eric; Miranda-Dominguez, Oscar; Fair, Damien; Wilson, Mark E.; Sanchez, Mar M.; Kelly, Clare
Abstract: In females, pubertal onset appears to signal the opening of a window of increased vulnerability to the effects of stress on neurobehavioral development. What is the impact of pubertal timing on this process? We assessed the effects of pubertal timing and stress on behavior and amygdala functional connectivity (FC) in adolescent female macaques, whose social hierarchy provides an ethologically valid model of chronic psychosocial stress. Monkeys experienced puberty spontaneously (n = 34) or pubertal delay via Lupron treatment from age 16–33 months (n = 36). We examined the effects of stress (continuous dimension spanning dominant/low-stress to subordinate/high-stress) and experimental pubertal delay (Lupron-treated vs. Control) on socioemotional behavior and FC at 43–46 months, after all animals had begun puberty. Regardless of treatment, subordinate monkeys were more submissive and less affiliative, and exhibited weaker FC between amygdala and dorsolateral prefrontal cortex and stronger FC between amygdala and temporal pole. Regardless of social rank, Lupron-treated monkeys were also more submissive and less affiliative but were less anxious and exhibited less displacement behavior in a "Human Intruder" task than untreated monkeys; they exhibited stronger FC between amygdala and orbitofrontal cortex. No interactions between rank and Lupron treatment were observed. These similar behavioral outcomes may reflect the common factor of delayed puberty – whether this is stress-related (untreated subordinate animals) or pharmacologically-induced (treated animals). In the brain, however, delayed puberty and subordination stress had separable effects, suggesting that the overlapping socioemotional outcomes may be mediated by distinct neuroplastic mechanisms. To gain further insights, additional longitudinal studies are required. Highlights: How does the timing of puberty interact with stress in the female adolescent brain? We examined how pharmacological puberty delay altered stress phenotypes in macaques. Induced puberty delay and subordination stress similarly altered behavior. Puberty delay and subordination differently altered amygdala functional connectivity. Puberty onset at late chronological age is associated with socioemotional alterations.